2022
DOI: 10.3390/genes13030462
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Clinical Studies of Peripheral Neuropathies with Three Small Heat Shock Protein Gene Variants in Korea

Abstract: Small heat shock proteins (sHSPs) are ATP-independent chaperones that help correct the folding of denatured proteins and protect cells from stress. Mutations in HSPB1, HSPB8, and HSPB3 are implicated in inherited peripheral neuropathies (IPNs), such as Charcot-Marie-Tooth disease type 2 (CMT2) and distal hereditary motor neuropathies (dHMN). This study, using whole exome sequencing or targeted gene sequencing, identified 9 pathogenic or likely pathogenic variants in these three sHSP genes from 11 Korean IPN fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Although PMP22 de novo mutations have been frequently reported by other studies [ 9 , 15 ], the rate was higher than those shown in the other CMT gene mutations in Korea compared to the 45.0% and 18.7% of the trio families with the MPZ mutations and PMP22 duplication causing CMT1A [ 47 ], respectively. Only two and one de novo cases were observed in 11 families with small heat shock protein (sHSP) gene mutations [ 48 ] and 13 families with aminoacyl tRNA-synthetase (ARS) gene mutations [ 49 ]. In particular, c.215C>T (p.S72L) de novo mutation, which was observed in 4 of 5 families with the corresponding mutation, is suggested to locate in a mutational hotspot.…”
Section: Discussionmentioning
confidence: 99%
“…Although PMP22 de novo mutations have been frequently reported by other studies [ 9 , 15 ], the rate was higher than those shown in the other CMT gene mutations in Korea compared to the 45.0% and 18.7% of the trio families with the MPZ mutations and PMP22 duplication causing CMT1A [ 47 ], respectively. Only two and one de novo cases were observed in 11 families with small heat shock protein (sHSP) gene mutations [ 48 ] and 13 families with aminoacyl tRNA-synthetase (ARS) gene mutations [ 49 ]. In particular, c.215C>T (p.S72L) de novo mutation, which was observed in 4 of 5 families with the corresponding mutation, is suggested to locate in a mutational hotspot.…”
Section: Discussionmentioning
confidence: 99%
“…Missense mutations of the K141 residue of HSPB8 have been associated with dHMN and CMT2L disease, which mainly targets motor neurons [ 11 , 12 , 14 ]. We found three mutations of the K141 residue (K141N, K141E, and K141T) in HSPB8 from a patient cohort with inherited peripheral neuropathy [ 21 ]. The vulnerability of motor neurons to mutated HSPB8 has been reported by overexpression studies in primary neuronal motor neuron cultures in which K141E and K141N HSPB8 caused neurite degeneration [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…One of the most common causes of dHMN are dominant mutations in HSPB1 , the prevalence of which vary between 5 and 10% in different series [3 ▪ –5 ▪ ,6,10]. Recessive inheritance has been reported in few cases [11,12]. Patients carrying the same HSPB1 mutation can be diagnosed with either dHMN or CMT2 [3 ▪ ].…”
Section: Classic Distal Hereditary Motor Neuropathiesmentioning
confidence: 99%